Digitization and Tourist Intelligence: an option to improve the profitability of the Chimbote hotel industry, 2022 (LACCEI, 2024)
Many businesses linked to the hotel industry have had serious difficulties to reactivate due to the health and economic situation that has been experienced since 2020 by COVID-19, seeing their profitability affected, compared to 2019. However, the Companies that have implemented digitization and tourism intelligence have been able to increase their sales in times of pandemic. However, the traditional hotel industry that has not been able to access these technologies has been relegated in its economic activities. In this sense, the objective was to determine the incidence of digitization and tourist intelligence as an option to improve the profitability of the Chimbote hotel industry, 2022. For this purpose, the study was of an applied type, likewise, its design was non-experimental., cross-correlational. The technique was the survey and the instrument the questionnaire, the population and sensible sample consisted of 11 hotels. The results indicate high levels in both variables, however there are several aspects to improve. Finally concluding that there is a highly significant relationship between digitization and tourism intelligence and profitability.